2015
DOI: 10.1590/s1984-82502015000200023
|View full text |Cite
|
Sign up to set email alerts
|

Stability indicating RP-LC-PDA method for the quantitative analysis of saxagliptin in pharmaceutical dosage form

Abstract: Saxagliptin is a potent and selective inhibitor of the enzyme dipeptidyl peptidase 4. It is effective in the treatment of type 2 diabetes mellitus because it stimulates the pancreas to produce insulin. In the present study, a liquid chromatography method was developed and validated to quantify the drug in tablets. This method was based on the isocratic elution of saxagliptin, using a mobile phase consisting of 0.1% phosphoric acid at pH 3. 0 -methanol (70: 30, v/v) at a flow rate of 1 mL.min -1 with UV detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…), is a potent, selective, long-acting, and reversible inhibitor of the enzyme dipeptidyl peptidase 4 (DPP-4) used for treatment of type 2 diabetes mellitus. It is used as monotherapy or in combination with other drugs (Scheeren et al, 2015;Hanan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), is a potent, selective, long-acting, and reversible inhibitor of the enzyme dipeptidyl peptidase 4 (DPP-4) used for treatment of type 2 diabetes mellitus. It is used as monotherapy or in combination with other drugs (Scheeren et al, 2015;Hanan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A few analytical methods were reported in the literature for the determination of SAXA alone. Stability indicating RP HPLC and RP-LC-PDA methods for determination of SAXA in pharmaceutical dosages were developed (Scheeren et al, 2015;Konari, Jacob, 2015). SAXA was estimated, with other antidiabetic drugs like vildagliptin, using spectrophotometric and spectrofluorimetric methods from bulk and pharmaceutical dosage forms (Marwa, 2013) and also with metformin hydrochloride, using the RP column liquid chromatographic method in binary mixtures (Mohammad, Ehab, Marwa, 2012), The HPLC method is used in active drug and pharmaceutical dosage forms (Hanan et al, 2017) and stability indicating RP HPLC method for the determination of saxagliptin and metformin in bulk and pharmaceutical product (Ramesh, Senthil Kumar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, it is (1S,3S,5S)-2-((2S)-amino(3-hydroxytricyclo(3.3.1.13,7)dec-1yl)acetyl)-2-azabicyclo(3.1.0) hexane-3-carbonitrile ( Figure 1b) and has the molecular formula C 18 H 25 N 3 O 2 . [7][8][9] A review of the literature revealed that a few analytical methods like LC-Mass spectrometry, 10,11 HPLC, [12][13][14][15][16][17][18][19] and spectroscopic methods 20,21 are available for the estimation of these drugs, either individually or in combination with other diabetic drugs like metformin. [22][23][24][25][26] The present work aimed to develop a simple, rapid, and accurate method for the estimation of dapagliflozin and saxagliptin in human plasma, as per US-FDA guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC, LC-MS and, GC has been reported for estimation of Dapagliflozin and Saxagliptin individually or in combination with other drugs. The reported methods are Spectrophotometric [9][10][11][12][13][14][15] , HPLC [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , LC-MS [36][37] and GC 38 method are reported for the simultaneous estimation of DAP and SAX in combined pharmaceutical formulation. Mobile Phase Preparation: Accurately weighed 2.72 g of Potassium dihydrogen phosphate transferred in a 1000 ml clean and dry volumetric flask, add about 900 ml of HPLC water and Sonicated for degassing and then finally make up the volume with water.…”
Section: Introductionmentioning
confidence: 99%